Supersimetria não-anticomutativa - Brito, Kelvyn Páterson Sousa de [UNESP] (2013)
In standard supersymmetry, we build a superspace with parameters 'x POT. 'mu'', 'teta', 'teta BARRA' that (anti)commute and super?elds that depend on them, then we impose constraints and de?ne chiral and vector super?elds, which are interesting examples, from which we build a supersymmetric Lagrangian. We will now impose a weaker condition on the superspace of the parameters: the ones that were anticommuting will now form a Cli?ord algebra {'teta' POT. 'alfa'', 'teta' POT. 'beta'}= 'C POT. 'alfa' 'beta'' (2) and, following an analogous procedure, with additional de?nitions, we will generalize our Lagrangian for the case of the non-anticommutative superspace